Керування матричним перетворювачем з використанням екстремальних положень просторових векторів керуючих функцій - Михальський, В.М.; Соболєв, В.М.; Шаповал, І.А.; Чопик, В.В. (Технічна електродинаміка, 2012)
The features of the matrix converter control to achieve the maximum expansion of the input reactive power control range have been considered. Analysis of the algorithm has been performed and qualitative output parameters of matrix converter have been obtained. Main optimization algorithm is presented.